Extracellular vesicles: Natural liver‐accumulating drug delivery vehicles for the treatment of liver diseases. Issue 2 (9th December 2020) - Zhang, Gensheng; Huang, Xiaofang; Xiu, Huiqing; Sun, Yan; Chen, Jiming; Cheng, Guoping; Song, Zhengbo; Peng, Yanmei; Shen, Yingying; Wang, Jianli; Cai, Zhijian
Abstract: Extracellular vesicles (EVs) are excellent potential vectors for the delivery of therapeutic drugs. However, issues with biological safety and disease targeting substantially limit their clinical application. EVs from red blood cells (RBC‐EVs) are potential drug delivery vehicles because of their unique biological safety. Here, we demonstrated that EVs, including RBC‐EVs, show natural liver accumulation. Mechanistically, the liver environment induces macrophages to phagocytize RBC‐EVs in a C1q‐dependent manner. RBC‐EVs loaded with antisense oligonucleotides of microRNA‐155 showed macrophage‐dependent protective effects against acute liver failure (ALF) in a mouse model. These RBC‐EVs were also effective in treatment of ALF. Furthermore, compared to routine doses of doxorubicin and sorafenib (SRF), RBC‐EVs loaded with doxorubicin or SRF showed enhanced therapeutic effects on a murine model of orthotopic liver cancer through a mechanism dependent on macrophages. Importantly, drug‐loaded RBC‐EVs showed no systemic toxicity at therapeutically effective doses, whereas routine doses of doxorubicin and SRF showed obvious toxicity. Thus, drug‐loaded RBC‐EVs hold high potential for clinical applications in the treatment of liver disease therapy.